2019
DOI: 10.18502/kss.v3i13.4202
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Islamic Financial Literacy through “Kencleng” Program in School

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In contrast to these research results, Aisyah & Saepuloh (2019) revealed that women's Islamic financial literacy is higher than men's [20]. This study is in line with Garg & Singh (2018) that women have higher literacy levels.…”
Section: Figure 1 Indonesian Financial Literacy Index Of Indonesia Year 2006 -2016supporting
confidence: 52%
“…In contrast to these research results, Aisyah & Saepuloh (2019) revealed that women's Islamic financial literacy is higher than men's [20]. This study is in line with Garg & Singh (2018) that women have higher literacy levels.…”
Section: Figure 1 Indonesian Financial Literacy Index Of Indonesia Year 2006 -2016supporting
confidence: 52%
“…From the results of this study, it can be seen that learning Islamic financial literacy is essential, accompanied by the application of appropriate learning (Aisyah & Saepuloh, 2019). The results of this study show practical implications.…”
Section: Discussionmentioning
confidence: 65%
“…Islamic financial literacy (IFL) refers to the knowledge and skills required to manage financial matters in accordance with Islamic principles (Abdullah & Anderson, 2015;Abdullah & Chong, 2014;Rahim, Rashid, & Hamed, 2016). IFL is important for the personal financial management of Muslims (Aisyah & Saepuloh, 2019;Kartawinata, Fakhri, Pradana, Hanifan, & Akbar, 2021;Rahman, Tajudin, & Tajuddin, 2018a). Among others, IFL helps to understand the functioning of Islamic finance and to avoid involvement in prohibited financial transactions (Ab Rahman, Tajudin, & Tajuddin, 2018;Nawi, Daud, Ghazali, Yazid, & Shamsuddin, 2018).…”
Section: The Moderating Effect Of Islamic Financial Literacy (Ifl)mentioning
confidence: 99%